O financiamento do Sistema Único de Saúde nas regiões de saúde do estado de Mato Grosso - Mendonça, Alessandra Félix (2012)
The Health System Funding, which has always been a critical issue becomes even more prominent with the momentum that has been given to the regionalization as a strategy to strengthen the SUS. This study aims to analyze the financing of SUS in the state of Mato Grosso, from 2002 to 2010, focusing the existing regions of health. Based on national information systems (SIOPS, SIA-SUS, SIH-SUS), as well as state documents and reports, we analyzed the health expenditures made by the 141 municipalities in Mato Grosso, organized into 16 regions of health. It was studied, besides the participation of the three spheres of government in health financing, if there were important differences in health spending given the specificities of those regions. In the nine years analyzed, there was a significant increase in expenditure on health per capita, made by the three levels of government. The per capita expenditures under the responsibility of municipalities also increased, ranging from 76% to 127% between the regions; in 2010 they accounted for R$ 437.54. The federal spending ranged from R $ 110.66 to R $ 243.38 between the regions, and in 11 of them at least 50% of these resources were focused on primary care. The state resources, besides inferior than the federal, also increased, likewise focused on primary care in 12 regions. With state funds, hospital care was addressed to specific regions and years, not necessarily linked to regional hospitals. The research highlights the complexity of health financing and the difficulty of analyzing it focused on regionalization. Despite the study limitations, it is believed that the results clarify some issues, provide useful information to managers and other stakeholders and raise numerous questions, paving the way for further investigations.